Survival outcome of Out-of-Hospital Cardiac Arrest in Emergency Medical Service with and without Physician Staffed - Buranasakda, Marturod; Wangsri, Kanya; Ienghong, Kamonwon; Kotruchin, Preaw; Rattanaseeha, Wutchara (Srinagarind Medical Journal, 2017)
Objective: Thai Emergency Medical Service (EMS) system aims to provide a good service for Thai people to assess the quick management for emergency patients. As to give a good service, it is believed that to have the physician on scene with ambulance in critical cases and cardiac arrest patients will give a better care. For evaluation the outcome of having physician on scene, we studied on the survival outcome of Out-of-Hospital cardiac arrest in EMS with and without physician staffed. Methods: This was a retrospective descriptive study, to compare the survival outcome of Out-of-Hospital cardiac arrest in EMS with and without physician staffed during 1 January 2013 to 31 December 2015 at Srinagarind hospital Result: Eighty-seven prehospital cardiac arrest patients enrolled in this study. Sixty-six cases had physician staffed EMS, and 31 of them had returned of spontaneous circulation at Emergency Department (46.97%). Seven patients in physician staffed with the EMS group had survived to discharge (10.60%). There were 21 patients received the initial resuscitation by EMS personnel, without physician in the team and 9 of them had returned of spontaneous circulation at the Emergency department (42.86%). Two patients in non-physician staffed EMS group had survived to discharge (9.52%).There was no difference in survival outcome at the Emergency department and survival to discharge with or without physician staffed EMS (p = 0.742, 0.642) Conclusions: There was no difference in survival outcome at Emergency department and survival to discharge with or without physician staffed Emergency Medical Service อัตราการรอดชีวิตในผู้ป่วยหัวใจหยุดเต้นนอกโรงพยาบาลเมื่อมีและไม่มีแพทย์ร่วมออกเหตุ หลักการและวัตถุประสงค์: ระบบบริการการแพทย์ฉุกเฉินไทย มีความมุ่งหวังให้คนไทยได้รับบริการทางการแพทย์ฉุกเฉินได้รวดเร็วและทันท่วงที มีการจัดให้แพทย์ร่วมออกเหตุให้การรักษานอกโรงพยาบาลในผู้ป่วยวิกฤตและผู้ป่วยหัวใจหยุดเต้น เพื่อเป็นการประเมินผลถึงผลลัพธ์ของการรักษาผู้ป่วยนอกโรงพยาบาลของแพทย์จึงนำมาสู่การศึกษาเปรียบเทียบอัตราการรอดชีวิตของผู้ป่วยหัวใจหยุดเต้นนอกโรงพยาบาลเมื่อมีและไม่มีแพทย์ร่วมออกเหตุ วิธีการศึกษา: เป็นการศึกษาแบบ Retrospective descriptive เปรียบเทียบถึงอัตราการรอดชีวิตที่ห้องฉุกเฉินในผู้ป่วยหัวใจหยุดเต้นนอกโรงพยาบาลที่ได้รับการนำส่งโดยระบบบริการการแพทย์ฉุกเฉิน โรงพยาบาลศรีนครินทร์ ในกลุ่มที่มีและไม่มีแพทย์ร่วมออกเหตุระหว่างวันที่ 1 มกราคม 2556 ถึง 31 ธันวาคม 2558 ผลการศึกษา: จากผู้ป่วยทั้งหมด 87 ราย แบ่งเป็นกลุ่มมีแพทย์ร่วมออกเหตุนอกโรงพยาบาลจำนวน 66 ราย และกลุ่มไม่มีแพทย์ร่วมออกเหตุนอกโรงพยาบาลจำนวน 21 ราย ในกลุ่มมีแพทย์ร่วมออกเหตุนอกโรงพยาบาลพบว่ามีจำนวน 31 ราย รอดชีวิตที่ห้องฉุกเฉิน (ร้อยละ46.97) และมี 7 ราย ที่สามารถรอดชีวิตกลับบ้านได้ (ร้อยละ10.60) ส่วนในกลุ่มที่ไม่มีแพทย์ร่วมออกเหตุนอกโรงพยาบาลพบมี 9 รายรอดชีวิตที่ห้องฉุกเฉิน (ร้อยละ42.86) และมี 2 ราย ที่รอดชีวิตกลับบ้านได้ (ร้อยละ 9.52) จากผลการศึกษาไม่พบมีความแตกต่างของอัตราการรอดชีวิตที่ห้องฉุกเฉิน (p = 0.742) และอัตราการรอดชีวิตกลับบ้าน (p = 0.642) ในกลุ่มที่มีแพทย์และไม่มีแพทย์ร่วมออกเหตุ สรุป: ไม่พบความแตกต่างของอัตราการรอดชีวิตที่ห้องฉุกเฉินและอัตราการรอดชีวิตกลับบ้านเมื่อมีและไม่มีแพทย์ร่วมออกเหตุ